Relationship among bacterial vaginosis, local inflammatory response and presence of cervical intraepithelial neoplasia in women with and without human papilloma virus infection - Antovska, Vesna; Basheska, Neli; Grncarova, Zlatka; Aleksioska, Natasha (Korean Society of Obstetrics and Gynecology, 2012)
Objective: An assessment of influence of human papilloma virus (HPV) infection on the presence of dysplasia and relationship among the local immune system, HPV infection and bacterial vaginosis (BV). Methods: The study group (n = 143) was divided into: experimental arm: positive HPV-DNA sequence with polymerase chain reaction method on the cervix tissue specimen (HPV group, n = 82), control arm: negative HPV-DNA sequence (nHPV group, n = 61). Secondarily, the study group was divided into: subgroup with malignant lesions (ML group, n = 95) and subgroup with benign lesions (BL group; n = 48). Each patient was evaluated for: bacterial morphotype (Nugent score), cervical inflammation, HPV cervical infection classified by virus subtype, histopathological examinations of the cervix biopsy. Results: In HPV group there was higher prevalence of women who: had their first sexual contact between 16 and 22 years (P < 0.001), had more than 3 previous or actual sexual partners (P < 0.001, P < 0.05; respectively), were unmarried (P < 0.01). We found: significantly higher prevalence of polymorphonuclear cervicitis and Candida albicans (C. albicans)-hyphae predomination in HPV group, but Gardnerella vaginalis in nHPV group, predomination of benign lesions in nHPV group, prevalence of Trichomonas vaginalis, as well as normal vaginal flora in BL subgroup, but C. albicans -sporae in ML subgroup. The most frequent infections in HPV group were those with HPV type 16 and 53. Conclusion: The local inflammatory response is predominantly expressed by mononuclear infiltration in HPV presence, probably as a result of declined local immunity. In these circumstances, the commensalisms (i.e., C. albicans) flourish.
Erratum: Relationship among bacterial vaginosis, local inflammatory response and presence of cervical intraepithelial neoplasia in women with and without human papilloma virus infection. "Korean J Obstet Gynecol 2012;55(7):468-476, this article was published with the orders of the authors' first and last names given incorrectly. Also, Korean J Obstet Gynecol 2012;55(9):692, in the published erratum for the authors' name correction, the bibliographic information (the issue number, page range, and DOI) of the original paper was given incorrectly." https://doi.org/10.5468/KJOG.2012.55.10.795
Keywords: Bacterial vaginosis; Cervical intraepithelial neoplasia; Human papilloma virus; Active immune response